Boosting photochemical activity by Ni doping of mesoporous CoO nanoparticle assemblies - Velegraki, Georgia; Vamvasakis, Ioannis; Papadas, Ioannis T.; Tsatsos, Sotiris; Pournara, Anastasia; Manos, Manolis J.; Choulis, Stelios A.; Kennou, Stella; Kopidakis, Georgios; Armatas, Gerasimos S. (My University, 2019)
The rational design of semiconductor nanostructures is of utmost importance for efficient solar energy conversion and environmental remediation. In this article, we report high-surface-area mesoporous networks consisting of Ni-implanted cubic CoO (Co 1-x Ni x O) nanoparticles as promising catalysts for the detoxification of aqueous Cr(vi) solutions. Mechanistic studies with X-ray photoelectron, UV-vis optical absorption, fluorescence and electrochemical impedance spectroscopy and theoretical (DFT) calculations indicate that the performance enhancement of these catalysts arises from the high charge transfer kinetics and oxidation efficiency of surface-reaching holes. By tuning the chemical composition, the Co 1-x Ni x O mesoporous catalyst at 2 atomic% Ni content imparts outstanding photocatalytic Cr(vi) reduction and water oxidation activity, corresponding to an apparent quantum yield (QY) of 1.5% at λ = 375 nm irradiation light.
Keywords: Chemical compositions; Environmental remediation; UV-vis optical absorption; Photochemical activity; High surface area mesoporous